Optimalisasi Komunikasi Humas dalam Membangun Brand Image SMAN 4 Mataram - Kadek Artadi; I Wayan Astraguna; Sayu Kadek Jelantik (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the public relations communication strategy in building the brand image of SMAN 4 Mataram in the digital era, as well as to identify the challenges faced and optimization efforts undertaken. The research is grounded in the growing demand for educational institutions to adapt to the dynamics of digital public communication. The theoretical framework is based on the Excellence Theory by Grunig & Grunig and the Brand Image theory by Aaker. A descriptive qualitative approach was employed, with the research subjects comprising the public relations team and the school principal, and the research objects focused on communication strategies and public perception. Informants included students, parents, alumni, and community members selected through purposive sampling. Data collection techniques included participatory observation, in-depth interviews, open-ended questionnaires, and document studies. Data were analyzed using Miles and Huberman’s interactive model. The findings reveal that the public relations communication strategy has been directed toward digital and collaborative efforts; however, it still encounters obstacles such as budget limitations, low public responsiveness, and insufficient human resource capacity. Optimization efforts have been carried out through media diversification, strengthening external relations, and innovating public communication programs.